Possible mechanisms of development of carcinoma of breast in patients with early-onset cataract - Singh, Kaushal Deep; Faridi, Shahbaz Habib; Lodhi, Mehershree (International Surgery Journal, 2017)
Background: A nation-wide population based retrospective cohort study from Taiwan in 2014 suggested a propensity of developing breast cancer in young females with early-onset cataract. One such patient presented to us who was a young non-obese female with a large lump in the right breast with skin nodules and bilateral painless progressive diminution of vision. Patient was diagnosed as locally advanced carcinoma of right breast with axillary metastasis (stage IIIB) and bilateral early-onset nuclear cataract. Mechanism of this possible association has never been described. Methods: A comprehensive online English literature search was done using various electronic search databases. Different search terms related to pathogenesis of carcinoma breast and cataract, and their possible association, were used. An advanced search was further conducted by combining all the search fields in abstracts, keywords, and titles. Results: We summarized the data from the searched articles and found that there are certain biochemical pathways and genetic associations that link cancer to cataract. We identified four specific links between carcinoma breast and cataract (in some cases even early-onset cataract). The four mechanisms which explained this possible association included metabolic syndrome, action of reactive oxygen species, genetic polymorphisms and environmental factors. Conclusions: The evidence linking early-onset cataract with cancer is relatively new so possible mechanisms of development of breast cancer in patients with early-onset cataract needs to be elucidated. These plausible connections can further help to take up large scale molecular, biochemical, epidemiological and clinical studies to investigate this association in terms of cause-effect relationship. The impact this association can have, on understanding cataract and cancer pathogenesis; and its potential in reducing cancer incidence in patients with EOC, can be profound.